Saddu Dzari’ah Menurut Imam Syafi’i dan Aplikasinya dalam Mu’amalat Maliyah - Nofrizal, Okri Nofrizal (Tasyri' : Journal of Islamic Law, 2025)
There are certain issues (mustajaddad) that cannot be found empirically from the texts, but the methodological framework is crystallized from the postulates which are qath'i as a form of Islamic law management method called Saddu Dzarî'ah. A mujtahid who initiated the istinbât methodological framework who is famous for his maqâshid is Imam Syafi'i  (past a way 204 H). It is unique, when someone justifies that Imam Shafi'i does not recognize Saddu Dzarî'ah. The purpose of writing this thesis is to answer the real view of Imam Shafi'i regarding Saddu Dzarîah.  This research belongs to the category of qualitative research based on document (text) studies that focus on Imam Syafi'i's views regarding Saddu Dzarî'ah in the process of finding Islamic law. The research process was carried out using the ushul fiqh and comparative fiqh approaches. The discussion in this study uses the document study method. After conducting an in-depth study and analysis of the book Al-Umm, it was found that Imam Shafi'i acknowledged Saddu Dzari'ah either as a proposition (mashadir Al-Ahkam) or as makharij fiqhiyah.